Bibliometric Analysis Toxicity Levels of MOBA Game Players Among Students and the General Public - Ningsih, Neng Cahya; Amnesty, Gary Gibran (West Science Interdisciplinary Studies, 2024)
Multiplayer Online Battle Arena (MOBA) games have become a global phenomenon in the gaming industry. This article aims to examine the evolution, impact, and social aspects of MOBA games. We analyzed various literature sources, including scientific journals, articles, and research reports relevant to the keyword "MOBA." In our analysis, we see the development of MOBA games from their beginnings as modified real-time strategy (RTS) games to become a very popular standalone game genre. We also investigated the influence of MOBA games on mental health, social behavior, and addiction rates among players. Abstract P-ISSN: 2302-8734 Abstract Additionally, we explore social aspects such as communication within teams, development of collaborative skills, and learning related to MOBA gaming. Our research results show that MOBA games have a significant impact on players, both positive and negative. In a positive aspect, this game can improve social skills, strategic thinking skills, and team coordination. http://jurnal.umt.ac.id/index.php/jt/index E-ISSN: 2581-0006 Multiplayer Online Battle Arena (MOBA) games have become a global phenomenon in the gaming industry. This article aims to examine the evolution, impact, and social aspects of MOBA games. We analyzed various literature sources, including scientific journals, articles, and research reports relevant to the keyword "MOBA." In our analysis, we see the development of MOBA games from their beginnings as modified real-time strategy (RTS) games to become a very popular standalone game genre. We also investigated the influence of MOBA games on mental health, social behavior, and addiction rates among players. Additionally, we explore social aspects such as communication within teams, development of collaborative skills, and learning related to MOBA gaming. Our research results show that MOBA games have a significant impact on players, both positive and negative. In a positive aspect, this game can improve social skills, strategic thinking skills, and team coordination. However, there is also a risk of high levels of addiction and mental health disorders associated with excessive use. This research provides in-depth insight into the MOBA gaming phenomenon and the importance of understanding social aspects and their impact. However, there is also a risk of high levels of addiction and mental health disorders associated with excessive use. This research provides in-depth insight into the MOBA gaming phenomenon and the importance of understanding social aspects and their impact. Keywords: Bibliometric, Online Games, MOBA, Toxicity, Student.